1999
DOI: 10.1136/thx.54.10.884
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic needle aspiration biopsy for the diagnosis of localised pulmonary lesions: a meta-analysis

Abstract: Background-Persisting controversy surrounds the use of transthoracic needle aspiration biopsy (TNAB) stemming from its uncertain diagnostic accuracy. A systematic review and meta-analysis was therefore conducted to evaluate the accuracy of TNAB for the diagnosis of solitary or multiple localised pulmonary lesions. Methods-Searches for English literature papers in Index Medicus (1963)(1964)(1965) and Medline (1966Medline ( -1996 were performed and the bibliographies of the retrieved articles were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 65 publications
1
57
0
3
Order By: Relevance
“…A recent meta-analysis by Lacasse et al [14]on the role of transthoracic needle aspiration cytology on the diagnosis of localized pulmonary lesion has put forward that the ‘suspicious’ findings on cytology specimens markedly increase the probability of malignancy, with a likelihood ratio of 15. However, Johnson [15]reviewed a series of 205 patients with the diagnosis of ‘suspicious’ of cancer and found that 32% of those cytological samples were subsequently found to have a benign cause.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Lacasse et al [14]on the role of transthoracic needle aspiration cytology on the diagnosis of localized pulmonary lesion has put forward that the ‘suspicious’ findings on cytology specimens markedly increase the probability of malignancy, with a likelihood ratio of 15. However, Johnson [15]reviewed a series of 205 patients with the diagnosis of ‘suspicious’ of cancer and found that 32% of those cytological samples were subsequently found to have a benign cause.…”
Section: Discussionmentioning
confidence: 99%
“…The yield is high for malignancy but much lower for benign lesions. [63][64][65] Bleeding and pneumothorax are the major risks. Pneumothorax occurs in 15% to 24% of instances and requires a chest tube in 6% to 7%.…”
Section: Ttnamentioning
confidence: 99%
“…Pneumothorax occurs in 15% to 24% of instances and requires a chest tube in 6% to 7%. 65,66 Thus, TTNA would be ill advised in patients with poor lung reserve. Studies in HM and HCT patients indicate a lower yield in the range of 50% to 78%, where the likelihood of malignant etiologies is less.…”
Section: Ttnamentioning
confidence: 99%
“…As many as 29% of patients whose conditions were not diagnosed as malignant on trans-thoracic needle biopsy were ultimately found to have carcinoma (5). According to literature reports, the sensitivity and specificity of lung biopsy are separately 86% and 98.8% while its sensitivity and specificity can reach 91%, 94% by combining with perspective and CT guidance (7,8). The accuracy of puncture is evidently related to the location, depth and size of lesions; for nodules <2 cm, the total diagnosis accuracy of CT-guided puncture is about 77.2% (9); while for Figure 2A, showing an expansible lesion within a rib; as the patient was asymptomatic with normal blood parameters, the consensus was to follow the lesion with a roentgenogram.…”
Section: Review Articlementioning
confidence: 99%